Student perception of peer teaching and learning in pathology: A qualitative analysis of modified seminars, fishbowls, and interactive classroom activities - Sumit Grover; Neena Sood; Anurag Chaudhary (Wolters Kluwer Medknow Publications, 2018)
Context: Peer-assisted teaching and learning (PTL) is being experimented in different medical universities worldwide. It is a learner-centered approach involving students through active learning strategies. Aims: To study the student perception of PTL in methods such as group-led seminars and fishbowls, in classroom through various interactive activities; compare and find out the student acceptability and efficacy of each of these methods in learning conceptual topics such as various types of anemia. Subjects and Methods: Medical students of second-year professional course were subjected to PTL in classroom during allotted teaching hours for 10 successive sessions using group-led modified seminars, fishbowls, and different formality-level interactive activities such as street plays, prop sessions, quiz sessions, to make them understand the clinical features and presentation of different types of anemia through understanding of etio-pathogenesis. To ascertain the aspects that influenced learning, focus group discussions were conducted in small groups consisting of 14 students and one facilitator in each group. Qualitative thematic analysis was performed on transcripts of the audio recordings by authors. Results: The emerging themes from qualitative analysis of transcripts were pertaining to teacher, student, and organization. We found motivation, interest, and involvement of peer teacher, student behavior and collaboration, contact time between students and facilitator, preparation time, coherence with other curricular activities, group size and composition, suitability of topic for the kind of activity, and availability of material for preparation as few sub-aspects affecting learning. Conclusion: For PTL to be effective, adequate transfer of knowledge through good peer teacher involvement, learner receptiveness, and adequate contact time is needed. Proper preparation with suitability of topics for the type of activity, alignment of seminars with other activities, and course coherence are prerequisites for the same.